Analysis of Satisfaction Level of Teaching Activities of Junior High School Teachers in Bandung on The Use of Zoom Meeting Application with PIECES Method and Customer Satisfaction Index Calculation Techniques - I, Wellyne Victoria; Sihotang, Jay Idoan (8ISC Abstract Proceedings, 2022)
Coronavirus originating from Wuhan, Hubei Province – China, has spread rapidly throughout the world. Who (World Health Organization) named this disease, precisely in March 2020, as COVID-19. The health crisis created by the Covid-19 pandemic has had an impact on the education sector. The Government of Indonesia made the policy as an act of termination of the rapid spread of the virus. All face-to-face learning activities are stopped and replaced with online learning. With the change in learning habits, meeting applications appear that can help us in conducting online activities, especially online learning activities. Adventist College School in Bandung conducts online learning activities with the help of the Zoom Meeting application. The purpose of this study is to find out how much satisfaction levels of teachers of Adventist College Schools in Bandung in using the Zoom Meeting application as an online learning medium during the Covid-19 pandemic. In this study, Zoom Meeting application service quality measurement using PIECES Framework method with questionnaire data containing performance indicators, information indicators, economies indicators, control indicators, efficiency indicators, and service indicators. And the technique used in calculating the results of satisfaction levels is the Customer Satisfaction Index. Data collection techniques by distributing the questionnaires using google form. And from this study, the data of the research can provide an overview of the user satisfaction of the Zoom Meeting application and indirectly provide knowledge about how well the Zoom Meeting application can help us in communicating and conducting various activities with many people who are far away from us during this pandemic that does not allow us to come face to face with many people. In this case, Adventist Schools in Bandung. Keywords : user satisfaction, PIECES Framework, Zoom Meeting application, online learning, Customer Satisfaction Index